"Culture de la pauvreté" et analyse des Classes - Bernier, Bernard (Anthropologica, 2022)
Recently, American social scientists have devoted a good number of studies on the "Poor". This particular article presents a critique of the main trends represented in these studies. The author insists on their inability to identify causal factors and present an alternative framework of analysis based on historical materialism.